Characteristics of fever in patients with COVID-19 at presentation and after initiation of treatment - Ali Fawzi Abd alsahib; Doaa Faris Jabaz; Akeel M. Hamza; Anwar Jasib Almzaiel (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: COVID-19 infection manifests itself in a variety of ways, from asymptomatic/mild symptoms to death or serious illness. Coughing, shortness of breath, and fever are all common symptoms. Other symptoms include weakness, muscle discomfort, lethargy, sore throat, breathing problems, and loss of smell and/or taste. COVID-19 is diagnosed utilizing clinical indicators, CT scans or chest x-rays, serological tests, and molecular diagnostics of the viral genome using RT-PCR. Aim of the study: In the current study we aimed to shed light on the duration of fever, the most important symptom of the disease, and its association with other patients’ characteristics. Patients and methods: The current cross-sectional study was conducted in Iraq’s Al-Diwaniyah Province, which is located in the Mid-Euphrates region. The study included 99 COVID-19 cases, 50 males and 49 females ranging in age from 16 to 81 years. Age, gender, WBC count, lymphocyte percent, lung involvement assessed by CT-scan, duration of fever at time of presentation, and duration until fever subsides following initiation of treatment were the main variables studied in the current study, in addition to the presence of chronic medical illnesses such as diabetes mellitus, systemic hypertension, asthma, and pulmonary tuberculosis. Results: The mean age of all enrolled patients was 50.38 ±16.27 years and there was no significant difference in mean age between males and females (p = 0.924). There was also no significant difference in mean WBC count and lymphocyte % between males and females (p > 0.05). Lung involvement according to CT-scan was ranging from 0 -80 % and the mean was 26.77 ±21.43 %; there was no significant difference in mean lung involvement between males and females (p = 0.770). The mean duration of fever at time of presentation in all enrolled patients was 6.61 ±3.60 days and it ranged from 1 to 21 days. Duration of subside of fever was ranging from 2 -25 days in all patients with a mean of 5.82 ±3.53 days; there was no significant difference in mean duration between males and females (p = 0.214). The duration needed for fever to subside was positively and significantly correlated to WBC count, the duration of fever at presentation and to the presence of diabetes mellitus (p < 0.05). Conclusion: Longer duration of fever after diagnosis and treatment of COVID-19 can be predicted by high WBC count, longer duration of fever and presence of diabetes and those patients can be at high risk of severe complications and death.